2001
DOI: 10.1046/j.1523-1739.2001.99499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness in Conservation Practice: Pointers from Medicine and Public Health

Abstract: Practical conservation activity is increasing globally and is being undertaken by many different government and nongovernmental organizations. In the majority of cases, justification for proposed actions is experience-based rather than evidence-based, action is often taken without monitoring or evaluation of effectiveness, and results are rarely widely disseminated. Conservation has been compared with medicine as a crisis discipline in which action is often required urgently in the absence of good information.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
224
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(228 citation statements)
references
References 11 publications
0
224
0
4
Order By: Relevance
“…Specifically, we aimed to quantify the: (1) time taken for scientific information to be available to end-users in published format; (2) proportion of scientific articles freely available to end-users; and (3) the clarity in which the conservation and management implications of a research article are articulated to end-users. Furthermore, given suggestions that a stronger emphasis should be placed on the systematic development of review papers to provide decision makers with digestible and accessible information (Pullin and Knight, 2001;Sutherland et al 2004), we also quantify the extent to which review papers may assist in overcoming these barriers. In addressing these aims, we generated recommendations to overcome barriers relating to science accessibility, to promote more efficient uptake of science by environmental practitioners and allow the implementation of adaptive governance structures.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we aimed to quantify the: (1) time taken for scientific information to be available to end-users in published format; (2) proportion of scientific articles freely available to end-users; and (3) the clarity in which the conservation and management implications of a research article are articulated to end-users. Furthermore, given suggestions that a stronger emphasis should be placed on the systematic development of review papers to provide decision makers with digestible and accessible information (Pullin and Knight, 2001;Sutherland et al 2004), we also quantify the extent to which review papers may assist in overcoming these barriers. In addressing these aims, we generated recommendations to overcome barriers relating to science accessibility, to promote more efficient uptake of science by environmental practitioners and allow the implementation of adaptive governance structures.…”
Section: Introductionmentioning
confidence: 99%
“…The value of evidence reviews to end-users is strongly dependent on review objectivity (i.e. the review methodology reduces the susceptibility of findings to bias, individual judgement, or prejudice) and comprehensiveness (Chalmers, 2003;Pullin and Knight, 2001;Rothstein et al, 2013). These qualities also assist researchers in identifying gaps in knowledge and areas of controversy or uncertainty, and can help decision-makers undertake informed management and defend potentially controversial or expensive actions (Gough et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of evidence is not exclusive to bushmeat research and interventions: it has been recognized as a serious obstacle to effective conservation by a growing number of scholars and practitioners (Knight et al, 2006;Sutherland et al, 2004;Pullin and Knight, 2001) who have suggested that 'current conservation practice is based upon anecdote and myth rather than upon the systematic appraisal of the evidence' (Sutherland et al, 2004). Establishing an evidence base can inform current and future project design, improve cost-effectiveness and ensure that funding is allocated to projects with the highest impact potential (Ferraro and Pattanayak, 2006).…”
Section: Introductionmentioning
confidence: 99%